Emotional Intelligence as a Predictor of Improving Mathematics Performance Through Anxiety and Motivation Management - Patimah, Lamlam; Widianjani , Widianjani; Saniah, Lia (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the influence of emotional intelligence on students’ mathematics performance, focusing on the mediating roles of anxiety management and learning motivation. Method: A quantitative survey method was employed with 172 purposively selected vocational high school students. Research instruments were validated and tested for reliability, and data were analyzed using path analysis with SPSS 22. Results: The findings reveal that emotional intelligence does not significantly affect mathematics performance directly but has a significant indirect effect through anxiety management and learning motivation. Learning motivation emerged as the most dominant mediator, and the path model explained 74.3% of the variance in mathematics performance. Novelty: This study advances Indonesian vocational school literature by introducing a path model that explains emotional intelligence as an indirect predictor of mathematics performance through anxiety management and learning motivation. Unlike previous SMK studies that focused on direct effects using simple regression, this research provides a process-oriented explanation by simultaneously modeling multiple mediators, offering a clearer understanding of how emotional and motivational factors shape mathematics achievement.